Evaluation of seaports’ investment attractiveness - Olena Palyvoda; Oksana Karpenko; Valentyna Vlasova; Nataliia Bondar; Olga Mishulina (Investment Management & Financial Innovations, 2020)
Ukraine’s European integration requires the involvement of seaports in the international TEN-T network, so it is extremely important to create favorable investment conditions to develop port infrastructure. This study aims to make a comprehensive assessment of the seaports’ investment attractiveness to use it for increasing the efficiency of attracting investment in the development of Ukrainian seaports, which are part of the European transport network. The study was conducted using the Saati method and the method of calculating the integrated indicator of seaports’ investment attractiveness. The integrated indicator includes assessing indicators of business activity in the region and consolidated indicators of financial and property status, logistical attractiveness, and prospects for port development. According to the results of calculations, the seaports of Ukraine were divided into three groups. The ports of Yuzhne, Odesa, Illichivsk, and Mykolaiv have a high level of investment attractiveness. The ratio of investment attractiveness ranges from 3 to 2.6. The ports of Izmail, Mariupol, Oktyabrsk, and Kherson have an average level (ratio from 2.2 to 1), and other ports have a low investment attractiveness (coefficient from 0.9 to 0.7).